2014
DOI: 10.1093/treephys/tpu086
|View full text |Cite
|
Sign up to set email alerts
|

Responses of gas-exchange rates and water relations to annual fluctuations of weather in three species of urban street trees

Abstract: The frequency of extreme weather has been rising in recent years. A 3-year study of street trees was undertaken in Tokyo to determine whether: (i) street trees suffer from severe water stress in unusually hot summer; (ii) species respond differently to such climatic fluctuations; and (iii) street trees are also affected by nitrogen (N) deficiency, photoinhibition and aerosol pollution. During the study period (2010-12), midsummers of 2010 and 2012 were unusually hot (2.4-2.8 °C higher maximum temperature than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 49 publications
4
7
0
Order By: Relevance
“…Similarly to our findings, many studies observed significantly reduced A rates in urban areas, which are characterized by limited water availability (Percival et al 2006, Osone et al 2014 and sealed surfaces (Wang et al 2019). The reduction of A under drought has been addressed to the protective mechanism of plants to avoid damage due to dehydration and hydraulic failure (Osone et al 2014).…”
Section: Discussionsupporting
confidence: 86%
“…Similarly to our findings, many studies observed significantly reduced A rates in urban areas, which are characterized by limited water availability (Percival et al 2006, Osone et al 2014 and sealed surfaces (Wang et al 2019). The reduction of A under drought has been addressed to the protective mechanism of plants to avoid damage due to dehydration and hydraulic failure (Osone et al 2014).…”
Section: Discussionsupporting
confidence: 86%
“…The mean stomatal density for G. biloba, 80.7 ± 1.4 mm -2 , is similar to most published values (McElwain and Chaloner, 1996;Beerling et al, 1998;Chen et al, 2001;Pandey et al, 2003;Sun et al, 2003;Smith et al, 2010;Osone et al, 2014), which range from ~61 -98 mm -2 . (Note that some of these values are estimated from plots.)…”
Section: Stomatal Measurementssupporting
confidence: 88%
“…I find a mean photosynthetic rate for G. biloba of 8.19 ± 0.24 μmol m -2 s -1 (Table 5.3). This rate is similar to that found for the species in at least one other study (Pandey et al, 2003), and lower than the rates measured by Osone et al (2014), but higher than many other published values (Beerling et al, 1998;Leigh et al, 2011;Franks et al, 2014) which are all close to 5 μmol m -2 s -1 . My mean stomatal conductance for G. biloba is similar to published values (Leigh et al, 2011;P.…”
Section: Gas Exchange Measurementssupporting
confidence: 84%
“…The stored carbon in sapwood would contribute to the homeostasis of forest ecosystems with reducing the hydraulic failure-induced forest die-offs. Such a mechanism is responsible for ongoing cases of forest die-offs for heating and drying in urban forests 38 . Under the chronic shortage in carbon resources induced by the progressing global changes, forest ecosystem may not be able to maintain the homeostasis.…”
Section: Discussionmentioning
confidence: 99%